Perolehan Siswa Setelah Mengikuti Layanan Konseling Perorangan (Studi Deskriptif terhadap Siswa di SMP Negeri 26 Padang)) - Ilya Rahmi Risno; Asmidir Ilyas; Syahniar Syahniar (Universitas Negeri Padang, 2013)
Individual counseling services are in guidance and counseling services that provide benefits to the students to alleviate personal problems. Various problems faced by students with respect to the acquisition of the students after attending individual counseling services. This study aims to determine student gains after attending individual counseling services. The study was descriptive, subject students who have completed individual counseling services in SMP Negeri Padang 26 students totaling 35 people. In general it was found that most students have gotten gains after attending individual counseling services both in terms of understanding, the form of the acquisition or expectation after attending individual counseling services.   Layanan konseling perorangan merupakan layanan dalam bimbingan dan konseling yang memberikan manfaat kepada siswa dalam mengentaskan permasalahan pribadinya. Berbagai permasalahan dihadapi siswa berkenaan dengan perolehan siswa setelah mengikuti layanan konseling perorangan. Penelitian ini bertujuan untuk mengetahui perolehan siswa setelah mengikuti layanan konseling perorangan. Jenis penelitian ini adalah deskriptif, subjeknya siswa yang sudah pernah mengikuti layanan konseling perorangan di SMP Negeri 26 Padang yang berjumlah 35 orang siswa. Secara umum ditemukan bahwa sebagian besar siswa sudah mendapatkan perolehan setelah mengikuti layanan konseling perorangan baik dari segi pemahaman, bentuk perolehan maupun harapan setelah mengikuti layanan konseling perorangan.